1995
DOI: 10.4141/cjas95-049
|View full text |Cite
|
Sign up to set email alerts
|

The effect of level of diet intake after mating on the serum concentration of thyroxine, triiodothyronine, growth hormone, insulin and glucose, and embryonic survival in the gilt

Abstract: . 1995. The effect of level of diet intake after mating on the serum concentration of thyroxine' triiodothyronine, growtir'hormone, insulin and glucose, and embryonic survival in the gilt. Can. J. Anim' Two experiments ,Jere undertaken to determine w-hether ih"." *ur a relationship between embryo survival and the blood serum concentration of thyroxine (T/, triiodothyronine 1T..1, growth hormone (GH), insulin (INS), glucose (Glc)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Thus, it is tempting to speculate that an increase in T4 and Tl seen on the second day of food deprivation might be due to the psychological stress. Dyck and Kennedy (1995) found that in early pregnant gilts the postprandial effect on T4 was an immediate rise in concentration, while T3 peaked at 1.5 h. Overall there were no differences in thyroid hormones concentrations as well as in the embryo a1 between food restricted and control gilts (Dyck and Kennedy, 1995). The results from Mburu's et al (1997) study indicate that depriving inseminated sows of food shortly after ovulation, lowered the cleavage rate of their embryos, and decreased sperm numbers in the oviduct reservoir, as reflected by the sperm numbers counted in the zona pellucida.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is tempting to speculate that an increase in T4 and Tl seen on the second day of food deprivation might be due to the psychological stress. Dyck and Kennedy (1995) found that in early pregnant gilts the postprandial effect on T4 was an immediate rise in concentration, while T3 peaked at 1.5 h. Overall there were no differences in thyroid hormones concentrations as well as in the embryo a1 between food restricted and control gilts (Dyck and Kennedy, 1995). The results from Mburu's et al (1997) study indicate that depriving inseminated sows of food shortly after ovulation, lowered the cleavage rate of their embryos, and decreased sperm numbers in the oviduct reservoir, as reflected by the sperm numbers counted in the zona pellucida.…”
Section: Discussionmentioning
confidence: 99%
“…Spencer (1 994) reported that cortisol and T3 rose to peak levels 15-20 min after pigs were subjected to a loading stress. Food restriction in gilts resulted in the elevated progesterone production without a concomitant increase in thyroxine (T4) and T3 but had no negative effect on the embryo survival (Dyck and Kennedy, 1995). In our previous study (Tsuma et al, 1996) we reported progesterone, cortisol and PGF2, metabolite to be increased in the fasted early pregnant sows, which had numerically lower embryonic al than the control animals.…”
Section: Introductionmentioning
confidence: 94%